2014
DOI: 10.1007/jhep08(2014)172
|View full text |Cite
|
Sign up to set email alerts
|

Portrait of a colour octet

Abstract: New colour octets stand out among the new physics proposals to explain the anomalous forward-backward asymmetry measured in tt production by the CDF experiment at the Tevatron. We perform a fit to tt observables at the Tevatron and the LHC, including total cross sections, various asymmetries and the top polarisation and spin correlations, to find the most likely parameters of a light colour octet to be consistent with data. In particular, an octet coupling only to right-handed quarks gives a good fit to all me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 97 publications
(117 reference statements)
3
30
0
Order By: Relevance
“…The various constraints from tt observables on the parameter space of a light octet with this mass and width were analysed in full detail in ref. [43]. Here we only include the most relevant constraints, namely…”
Section: Predictions For Ttmentioning
confidence: 99%
“…The various constraints from tt observables on the parameter space of a light octet with this mass and width were analysed in full detail in ref. [43]. Here we only include the most relevant constraints, namely…”
Section: Predictions For Ttmentioning
confidence: 99%
“…The inclusive measurement of A C and A tt C is furthermore compared to two models of physics beyond the Standard Model (BSM) [9] that could be invoked to explain an anomalous forward-backward asymmetry at the Tevatron, such as reported by the CDF experiment [24]. Two models with a new colour octet particle exchanged in the s-channel are considered.…”
Section: Bin Of ∆|η|mentioning
confidence: 99%
“…It is the only quark in the Standard Model (SM) that decays before hadronization occurs, and the only quark with Yukawa coupling to the Higgs boson close to unity. A precise study of top quark properties could shed light on possible physics models beyond the SM [3][4][5][6][7][8][9]. This analysis uses a data set corresponding to an integrated luminosity of 4.6 fb −1 of Large Hadron Collider (LHC) proton-proton (pp) collisions at a centre-of-mass energy of 7 TeV collected by the ATLAS detector.…”
mentioning
confidence: 99%
“…In particular, in ref. [60] it could be demonstrated that a fit of top quark measurements at the Tevatron and the LHC performed within the SM is improved considerably if a light axigluon is included in the theory (compare also [61][62][63][64][65] for model constraints from other measurements).…”
Section: Jhep09(2014)084mentioning
confidence: 99%